Clinical morbidity associated with Schistosoma haematobium infection in pre‐school age children from an endemic district in Zimbabwe. Issue 9 (9th July 2020) - Mduluza‐Jokonya, Tariro L.; Naicker, Thajasvarie; Kasambala, Maritha; Jokonya, Luxwell; Vengesai, Arthur; Midzi, Herald; Choto, Emilia; Musonza, Kimpton; Rusankaniko, Simbarashe; Sibanda, Elopy; Mutapi, Francisca; Mduluza, Takafira
Abstract: Objective: To investigate Schistosoma haematobium morbidity in infected pre‐school age children and establish their disease burden. Methodology: Pre‐school age children (1–5 years) who were lifelong residents of the study area and had no other infections were included in the study. Participants underwent a physical examination with clinicians blinded to their infection status. Diagnosis of S. haematobium was by urine filtration. Results: The prevalence of S. haematobium was 35.1% (146/416). The clinical features observed in patients with Schistosoma haematobium were as follows: wheezes (morbidity attributable factor (AF = 93.9%), haematuria (AF = 92.6%), ascites (AF = 91.5%), atopy (AF = 76.9%), inguinal lymphadenopathy (AF = 68.4%), stunting (AF = 38.2), malnutrition (MUAC)(AF = 20%) and weight for height scales (AF = 5%). Schistosoma. haematobium infected children were at greater odds ratio of presenting with inguinal lymphadenopathy (AOR)=99.2(95% CI 24.2 to 854.5), wheezes in the chest (AOR = 35.4 95% CI 15.3 to 94.2), Distended abdomen with ascites (AOR = 23.9 95% CI 11.4 to 54), haematuria (AOR = 12.6 95% CI 11.6 to 14.1), atopy history (AOR = 5.6 95% CI 1.85 to 20.2), malnutrition (AOR = 2.3 95% CI 1.4 to 3.2) and stunting (AOR = 1.9 95% CI 1.1 to2.7). Conclusion: The study is novel as it demonstrates for the first time clinical morbidity markers associated with S. haematobium infection in pre‐school age children. Furthermore the study adds scientific evidence to the call for inclusion of pre‐school age children in schistosomiasis control programmes. These morbidity markers highlight the need for early diagnosis and screening for S. haematobium in pre‐school age children. Abstract : Objectif: Etudier la morbidité de Schistosoma haematobium chez les enfants d'âge préscolaire infectés et établir sa charge de morbidité. Méthodologie: Les enfants d'âge préscolaire (1 à 5 ans) qui avaient toujours résidents de la zone d'étude et qui n'avaient pas d'autres infections ont été inclus dans l'étude. Les participants ont subi un examen physique avec des cliniciens en aveugle sur leur état d'infection. Le diagnostic de S. haematobium a été effectué par filtration d'urine. Résultats: La prévalence de S. haematobium était de 35, 1% (146/416). Les caractéristiques cliniques observées chez les patients infectés par S. haematobium étaient: respiration sifflante (facteur attribuable à la morbidité (FA = 93, 9%), hématurie (FA = 92, 6%), ascite (FA = 91, 5%), atopie (FA = 76, 9%), lymphadénopathie inguinale (FA = 68, 4%), retard de croissance ( AF = 38, 2), malnutrition (MUAC) (AF = 20%) et poids pour les échelles de taille (AF = 5%). Les enfants infectés par S. h aematobium présentaient un rapport de cotes plus élevé de présenter une lymphadénopathie inguinale (AOR) = 99, 2 ; (IC95%: 24, 2 à 854, 5), respiration sifflante dans la poitrine (AOR = 35, 4 ; IC95%: 15, 3 à 94, 2), abdomen distendu avec ascite (AOR = 23, 9 ; IC95%: 11, 4 à 54), hématurie (AOR = 12, 6 ; IC95%: 11, 6 à 14, 1), antécédents d'atopie (AOR = 5, 6 ; IC95%: 1, 85 à 20, 2), malnutrition (AOR = 2, 3 ; IC95%: 1, 4 à 3, 2) et retard de croissance (AOR = 1, 9 ; IC95%: 1, 1 à 2, 7). Conclusion: L'étude est nouvelle car elle démontre pour la première fois des marqueurs cliniques de morbidité associés à une infection à S. haematobium chez des enfants d'âge préscolaire. En outre, l'étude ajoute des données scientifiques à l'appel à l'inclusion des enfants d'âge préscolaire dans les programmes de lutte contre la schistosomiase. Ces marqueurs de morbidité mettent en évidence la nécessité d'un diagnostic précoce et d'un dépistage de S. haematobium chez les enfants d'âge préscolaire.